High frequency model for power electronics capacitors. - Siami, S.
The study of metallized capacitor behavior at high frequencies points out the presence of series and parallel resonances that could lead to oscillations, perturbations and additional losses in power electronics apparatus. Starting from an already established analytical model of this resonance, we propose a method to elaborate equivalent circuits suiting circuit simulators. These models should help further investigations on high frequency properties of decoupling and snubber capacitors in commutation cells
Keywords: Capacitor impedance; Circuit simulators; Commutation cells; Dielectric film; Equivalent circuits; Frequency domain; High frequencies; High frequency model; High frequency properties; Losses; Magnetic components; Metallized capacitor behavior; Oscillations; Parallel resonances; Perturbations; Power electronics apparatus; Power electronics capacitors; Series resonances; Snubber capacitors; Time domain